2013
DOI: 10.1371/journal.pone.0073046
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Children's Receptive Vocabulary Development from Four to Eight Years in the Longitudinal Study of Australian Children

Abstract: Receptive vocabulary develops rapidly in early childhood and builds the foundation for language acquisition and literacy. Variation in receptive vocabulary ability is associated with variation in children's school achievement, and low receptive vocabulary ability is a risk factor for under-achievement at school. In this study, bivariate and multivariate growth curve modelling was used to estimate trajectories of receptive vocabulary development in relation to a wide range of candidate child, maternal and famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
149
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(169 citation statements)
references
References 37 publications
11
149
1
8
Order By: Relevance
“…Being a teenage parent was found to be a risk factor for delayed vocabulary skills in the MUSP cohort (O'Callaghan et al, 1995). By contrast, Taylor et al (2013) found teenage parenthood was associated with lower vocabulary knowledge in the LSAC cohort at the bivariate level, however, this association did not remain in the multivariate model when adjusting for other risk factors. Harrison and McLeod (2010) also utilised the LSAC data but included maternal age as a continuous variable and found that being older at the birth of the child was a protective factor against vocabulary delays.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Being a teenage parent was found to be a risk factor for delayed vocabulary skills in the MUSP cohort (O'Callaghan et al, 1995). By contrast, Taylor et al (2013) found teenage parenthood was associated with lower vocabulary knowledge in the LSAC cohort at the bivariate level, however, this association did not remain in the multivariate model when adjusting for other risk factors. Harrison and McLeod (2010) also utilised the LSAC data but included maternal age as a continuous variable and found that being older at the birth of the child was a protective factor against vocabulary delays.…”
Section: Introductionmentioning
confidence: 67%
“…Offspring of mothers from a nonEnglish Speaking Background have been shown to be at increased risk for vocabulary delays in both the LSAC and MUSP cohorts (Harrison & McLeod, 2010;O'Callaghan et al, 1995;Taylor et al, 2013) supporting theories of variation in language development when more than one language is spoken at home (e.g. Hemsley, Holm, & Dodd, 2006).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations